Cultural Constraints in the Eradication of Corruption in Indonesia - Effendi, Erdianto; Susanti, Heni (Corruptio, 2024)
Corruption is the enemy of mankind around the world. The eradication of corruption in Indonesia today is increasing if you look at the quantity. However, the massive efforts to eradicate corruption in Indonesia seem to have not been successful because corruption continues to occur. The problem can be formulated in this article, namely: Is culture an obstacle to efforts to eradicate corruption in Indonesia. Using a normative juridical research approach, it was found that one of the obstacles to the eradication of corruption is a cultural obstacle where corruption actors who are political figures and community leaders are often regarded as good people who must be defended. The main problem is that the culture that was originally considered noble by the community is misused in practice as a means of facilitating corruption.